THE EFFECT OF WORK MOTIVATION, SELF-EFFICACY, AND LEADERSHIP STYLE ON BUSINESS PRODUCTIVITY IN WOMEN-OWNED MSMES IN MEDAN CITY - Herry Praja Hasugian; Agnes Situmorang; Aditya Nugraha Lubis; Saimara AM Sebayang; Teuku Aliyuddinsyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This research examines how work motivation, self-efficacy, and leadership influence productivity levels in women-led micro, small, and medium enterprises (MSMEs) in Medan. The research is based on the importance of enhancing the role of the MSME sector, particularly those led by women, in strengthening regional economic resilience. The methodology employed is a quantitative approach through a survey of 96 female MSME entrepreneurs. Information was collected through questionnaire distribution, while data processing utilized multiple linear regression analysis using SPSS version 26 software. The findings indicate that individually, all independent variables—work motivation, self-efficacy, and leadership—have a positive and significant impact on business productivity. Among the three, self-efficacy demonstrates the strongest influence. Collectively, these three variables contribute significantly to productivity with a coefficient of determination (R²) of 0.634, indicating that more than 60% of the variation in business productivity can be explained by this model. These results reinforce the urgency of strengthening internal factors to boost the productivity of women-led MSMEs. Consequently, MSME empowerment programs need to be expanded not only to financial and technological access, but also to non-material aspects such as increasing work motivation, entrepreneur self-confidence, and adaptive and collaborative leadership skills to create competitive and sustainable businesses.